Fundamentals of momentum, heat, and mass transfer (John Wiley & Sons, Inc., 2008)
undamentals of Momentum, Heat, and Mass Transfer, now in its fifth edition, continues to provide a unified treatment of momentum transfer (fluid mechanics), heat transfer, and mass transfer. This new edition has been updated to include more coverage of modern topics such as biomedical/biological applications as well as an added separations topic on membranes. Additionally, the fifth edition will focus on an explicit problem-solving methodology that is thoroughly and consistently implemented throughout the text